Squatter housing transformations in Turkey after 2002: public choice perspective. Issue 4 (2nd October 2021) - Solak, Ali Osman
Abstract: This article uses the public choice perspective to examine the squatter housing transformations in Turkey implemented by the Justice and Development Party (Adalet ve Kalkinma Partisi, AKP) after 2002. AKP used the discourse of earthquake risk to the public for speeding up and legitimating transformation projects and reducing social opposition. However, in practice the principal purpose of these transformation projects has been to increase voter support for the AKP by increasing economic growth and employment, obtaining revenue, and using this revenue for social housing projects. This paper concludes that transformation projects, where economic goals have priority, stimulate the economy and satisfy the government in the short term but harm the transformation itself and the squatter community.